Investigations on the Occurrence and Associated Risk Factors of Avian Coccidiosis in Osun State, Southwestern Nigeria - Shola David Ola-Fadunsin (Journal of Parasitology Research)
Avian coccidiosis is one of the most important diseases of poultry and it is responsible for a large number of poultry mortalities worldwide. This study was carried out to investigate the occurrence and associated risk factors of avian coccidiosis in Osun State, Nigeria. Fecal samples were collected and examined from 5,544 avian species that were brought for treatment at the state veterinary hospitals over a 10-year period. Parameters such as age, sex, season, and species of birds were determined. Also, the months of the year were taken into consideration. Overall prevalence of 41.3% was recorded. The year specific rate for avian coccidiosis was highest in 2007 (97.9%) and lowest in 2006 (0.4%), while the month-specific rate was highest in November (85.7%) and lowest in July 2006 (13.3%). There was a significantly (P<0.05) higher prevalence in young birds compared to adults, in males compared to females, and during the wet season compared to the dry season. Broilers (99.8%) and cockerels (81.0%) were the bird types with the highest prevalence rate. The high prevalence of avian coccidiosis in the study area shows that the disease is endemic and there is need to embark on a radical preventive measure to curtail the disease.